Circumstantial deliveries - Needham, Rodney (Quantum books., 1981)
This simulating book gathers five lectures that ask questions of the broadest general intellectual interest: What is religion? Do other peoples have the same emotional states as we do? Why do humans make use of body imagery? In Circumstantial Deliveries, Rodney Needham shows that the comparative study of societies may furnish the answers. Circumstantial Deliveries challenges the methodology and substance of many conventional ideas about human nature and calls for more radical and comparative analyses. For instance, the author discredits the notion that to primitive peoples the colors red, white, and black symbolize blood, semen, and feces, respectively, arguing that an extensive comparative study of primitive societies discovered no such relationship. These essays sound a common theme: "If a deeper appreciation of the value of life can be had from reading Crime and Punishment, or if a more acute assessment of the springs of action can be acquired from Hamlet, then in principle it should be conceded that like benefits may be derived from a sympathetic observation of other men engaged in their daily affairs." This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1981.